Determinants of Intracerebral Hemorrhage Growth: An Exploratory Analysis - Broderick, Joseph P.; Diringer, Michael N.; Hill, Michael D.; Brun, Nikolai C.; Mayer, Stephan A.; Steiner, Thorsten; Skolnick, Brett E.; Davis, Stephen M. (Stroke (1970), 2007)
Background and Purpose— We report an exploratory analysis from a randomized study of recombinant activated factor VII (rFVIIa) in patients with intracerebral hemorrhage (ICH) examining potential factors associated with hemorrhage growth. Methods— We explored the relationship between 5 different measures of change in hemorrhage volume between baseline and 24-hour CTs (absolute and percent change in ICH volume, ICH growth—categoric [no growth if change <33% and <12.5 mL], absolute and percent change in ICH plus intraventricular hemorrhage [IVH] volume) and 31 demographic, clinical, imaging, historic, and baseline laboratory variables. Variables with a probability value of ≤0.10 were included in the final multivariable models. Results— Treatment with rFVIIa and a longer time-from-onset-to-baseline CT were related to a decrease in hemorrhage growth in all 5 models. ICH volume on baseline CT was consistently associated with ICH growth in the various models. Other variables significantly related to growth of ICH or ICH+IVH in at least 1 of the 5 models include serum glucose (increased levels associated with increased growth), body mass index (heavier people have less growth), prior use of antiplatelet agent (prior use associated with increased growth), serum cholesterol (higher level associated with less hemorrhage growth), and serum creatinine (higher level associated with more hemorrhage growth). Conclusions— Our exploratory analyses confirm that treatment with rFVIIa limits ICH growth in subjects with spontaneous ICH who met the criteria for this study. Most hematoma growth occurs early after onset of ICH. Larger hematomas on the baseline CT were associated with increased absolute ICH growth. The relationship of other factors to hemorrhage growth warrants further study.